2(x-4)5x=7

Simple and best practice solution for 2(x-4)5x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-4)5x=7 equation:


Simplifying
2(x + -4) * 5x = 7

Reorder the terms:
2(-4 + x) * 5x = 7

Reorder the terms for easier multiplication:
2 * 5x(-4 + x) = 7

Multiply 2 * 5
10x(-4 + x) = 7
(-4 * 10x + x * 10x) = 7
(-40x + 10x2) = 7

Solving
-40x + 10x2 = 7

Solving for variable 'x'.

Reorder the terms:
-7 + -40x + 10x2 = 7 + -7

Combine like terms: 7 + -7 = 0
-7 + -40x + 10x2 = 0

Begin completing the square.  Divide all terms by
10 the coefficient of the squared term: 

Divide each side by '10'.
-0.7 + -4x + x2 = 0.0

Move the constant term to the right:

Add '0.7' to each side of the equation.
-0.7 + -4x + 0.7 + x2 = 0.0 + 0.7

Reorder the terms:
-0.7 + 0.7 + -4x + x2 = 0.0 + 0.7

Combine like terms: -0.7 + 0.7 = 0.0
0.0 + -4x + x2 = 0.0 + 0.7
-4x + x2 = 0.0 + 0.7

Combine like terms: 0.0 + 0.7 = 0.7
-4x + x2 = 0.7

The x term is -4x.  Take half its coefficient (-2).
Square it (4) and add it to both sides.

Add '4' to each side of the equation.
-4x + 4 + x2 = 0.7 + 4

Reorder the terms:
4 + -4x + x2 = 0.7 + 4

Combine like terms: 0.7 + 4 = 4.7
4 + -4x + x2 = 4.7

Factor a perfect square on the left side:
(x + -2)(x + -2) = 4.7

Calculate the square root of the right side: 2.167948339

Break this problem into two subproblems by setting 
(x + -2) equal to 2.167948339 and -2.167948339.

Subproblem 1

x + -2 = 2.167948339 Simplifying x + -2 = 2.167948339 Reorder the terms: -2 + x = 2.167948339 Solving -2 + x = 2.167948339 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 2.167948339 + 2 Combine like terms: -2 + 2 = 0 0 + x = 2.167948339 + 2 x = 2.167948339 + 2 Combine like terms: 2.167948339 + 2 = 4.167948339 x = 4.167948339 Simplifying x = 4.167948339

Subproblem 2

x + -2 = -2.167948339 Simplifying x + -2 = -2.167948339 Reorder the terms: -2 + x = -2.167948339 Solving -2 + x = -2.167948339 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = -2.167948339 + 2 Combine like terms: -2 + 2 = 0 0 + x = -2.167948339 + 2 x = -2.167948339 + 2 Combine like terms: -2.167948339 + 2 = -0.167948339 x = -0.167948339 Simplifying x = -0.167948339

Solution

The solution to the problem is based on the solutions from the subproblems. x = {4.167948339, -0.167948339}

See similar equations:

| 6x+18=28-4x | | 3x-32=2(40-x) | | 4x+58=10+13 | | n^2+n+92=0 | | 3g=8-7g | | 34+13x=30+22x | | 0.9x-0.3(6-x)=2.4 | | n/10=3/5 | | pn=55 | | 13=-3(21-b)+2(b-2) | | 10x+7=4x-31 | | -4=2(d-3)-8 | | 0=15-3y-7x | | 9z+2-7z=56-7z | | 6x-32=2(40-x) | | -15k+9k=25 | | 2(s+2)+1=9 | | 11(z+3)-4(z-3)=3(z-4)+3(z-4) | | -61n-8=-8 | | 3y+1=x+4 | | 7x+7-8x=3x-3+x | | 5-u=10 | | 3x+4=44-2x | | 2h-h+5=19 | | 6x^3-36x^2-16x+3=0 | | -7a-3=-4a+7 | | 2x+3.3=8.1 | | 3(x+1)+2x=-2x-4(2x+3) | | 13=-7+6x | | x+5/8=(x/4)+(5/12) | | -2=-2(c-9) | | 14b^2c^3+21bc^5= |

Equations solver categories